Hubungan Sistem Pengendalian Internal dan Gaya Kepemimpinan Terhadap Kinerja Karyawan di Swan Keramas Bali - Ni Luh Putu Mita Miati; I Nyoman Sutapa; Putu Gede Wisnu Permana Kawisana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Employees play an important role in carrying out all company activities in order to grow to maintain the survival of the company. To create reliable human resources requires good management so that employee performance is more optimal. Internal Control and Effective leadership style are needed in a company organization to be able to improve the performance of all employees in achieving the goals set by the company. The research design used in this study is a survey method. The population in this study was all employees at Swan Keramas Villas Bali which amounted to 51 employees. To be able to better generalize then the sample in this study uses saturated samples. From the results of the study, the results of the Internal Control System have a positive effect on employee performance and leadership style has a positive effect on employee performance. In this study has a value of R Square of 0.696 then, for further research it is recommended to multiply the sample and add some variables